Porrhomma borgesi - Borges, Paulo A. V. (2021)
JUSTIFICATION: Porrhomma borgesi is an endemic money spider species occurring on three islands of the Azorean archipelago: Pico, Terceira and S. Miguel (Azores, Portugal) (Borges et al. 2010). It has a small Extent of Occurrence (EOO = ca. 8,312-8,500 km²) and a very small area of occupancy (AOO = 72-124 km²). The species is only abundant in very pristine sites (e.g. sites with a high habitat quality index sensu Gaspar et al. 2011) and is rare in most sites. Currently, invasive plants (Hedychium gardnerianum and Pittosporum undulatum) are impacting some of the areas and decreasing the quality of the habitat. Based on Ferreira et al. (2016) the habitat will further decline as a consequence of climate change. Therefore, we suggest as future measures of conservation: (1) regular monitoring of the species; and (2) control of invasive species namely Hedychium gardnerianum. Based upon the inferred decline in AOO, the decline in the quality and structure of habitat in some islands and number of locations the species is assessed as Vulnerable (VU).